2015
DOI: 10.1007/s11115-015-0310-6
|View full text |Cite
|
Sign up to set email alerts
|

Market-Type Mechanisms and Public Service Equity: A Review of Experiences in European Public Services

Abstract: The introduction of market-type mechanisms into the public sector has been a feature of many of the reforms associated with the New Public Management. In seeking to benefit from the competitive pressures exerted through marketization, governments have hoped to gain improvements in public service efficiency in particular. Yet, concerns remain about the effects of marketization on how equitably public services are provided, with many suggesting that there is an inevitable trade-off between efficiency and equity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Research suggests that vulnerable citizens are less likely to reap the benefits of market‐based service reforms (Anttonen ; Booltink et al . ; Botti and Iyengar ; Dan and Andrews ; Jilke ). Jilke (), for example, found that socio‐economic position is a significant determinant of the quality of services citizens will receive and their ability to switch from unsatisfactory providers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research suggests that vulnerable citizens are less likely to reap the benefits of market‐based service reforms (Anttonen ; Booltink et al . ; Botti and Iyengar ; Dan and Andrews ; Jilke ). Jilke (), for example, found that socio‐economic position is a significant determinant of the quality of services citizens will receive and their ability to switch from unsatisfactory providers.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that there is a trade‐off between equity and efficiency (Amirkhanyan ; Lerner ; Stiglitz ) and this was certainly found to be a concern amongst our participants. However, it is important to note that this is not borne out in the evidence to date, suggesting it may be a false dichotomy (Dan and Andrews , ). This would indicate that governments can engage in more stewardship type behaviour (to protect equity) without undermining the efficiency gains of markets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements in public service efficiency is the aim of implementation of this element. As an instance, Italy implemented contracting out in health care but lack of strategic planning and restricted efficiency gains through high transaction costs led to decrease in access and no change in efficiency 54 . It is reported that lack of effective patient charters and complaints system and informal payments had a negative effect on access and efficiency in Czech Republic, Russia, Ukraine, and Armenia health care system 55,56 .…”
Section: Discussionmentioning
confidence: 99%
“…Throughout recent years and decades, a number of European countries have liberalized their health care systems to various degrees [2,3]. The introduction of market mechanisms is intended to improve the quality of care and to contribute to cost containment.…”
Section: Introductionmentioning
confidence: 99%